Effects of 12 weeks of fascia knife release therapy in combination with exercise for treating neck and shoulder pain in adolescent table tennis players - Yunqing, Li; Shinian, Zhang; Jie, Li; Xianfeng, Wu (Frontiers in Public Health, 2025)
BackgroundWe investigated whether fascia knife release therapy combined with exercise for treating neck and shoulder pain administered over a period of 12 weeks enhanced the visual analog scale (VAS), cervical muscle endurance test (CMET) score and neck disability index (NDI) score in adolescent table tennis players.MethodsThis study adopted a prospective, exploratory design with a small sample size. The sample size was determined on the basis of the minimum requirements suggested by the relevant literature and feasibility considerations. Accounting for a potential 10% attrition rate, the study ultimately enrolled 40 adolescent table tennis players who were randomized to a control group or treatment group during the recovery period at the Anhui Sports Rehabilitation Clinic (Hefei, Anhui, China) in 2024. The subjects were divided into a medication group (n = 20, control group; CON) and a fascia knife release therapy combined with exercise group (n = 20, experimental group; EXP). A recovery exercise was applied to the control group for 12 weeks, whereas fascia knife release therapy combined with exercise was applied to the treatment group within the recovery empty period. The visual analog scale (VAS), cervical muscle endurance test (CMET) and neck disability index (NDI) were used to assess recovery before and after 12 weeks.ResultsComparisons of the visual analog scale (p = 0.854), cervical muscle endurance test (p = 0.393) and neck disability indices (p = 0.828) scores revealed no statistically significant differences between the CON group and the EXP group before the intervention. Compared with the control group, the EXP group presented significantly lower VAS (p = 0.001) and NDI (p = 0.001) scores following 12 weeks of fascia knife release therapy combined with exercise. There was a statistically significant increase in CMET in the treatment group (p = 0.001) compared with that in the CON group.ConclusionFascia knife release therapy combined with functional exercise enhances cervical muscle endurance (CMET) while significantly reducing pain (VAS) and functional disability (NDI) in adolescent table tennis players with neck and shoulder pain. Thus, this combined approach not only addresses immediate symptoms but also strengthens the muscles around the neck and shoulders, providing improved support and stability.